2012
DOI: 10.2147/ijn.s36714
|View full text |Cite
|
Sign up to set email alerts
|

Bone repair by periodontal ligament stem cell-seeded nanohydroxyapatite-chitosan scaffold

Abstract: Background: A nanohydroxyapatite-coated chitosan scaffold has been developed in recent years, but the effect of this composite scaffold on the viability and differentiation of periodontal ligament stem cells (PDLSCs) and bone repair is still unknown. This study explored the behavior of PDLSCs on a new nanohydroxyapatite-coated genipin-chitosan conjunction scaffold (HGCCS) in vitro as compared with an uncoated genipin-chitosan framework, and evaluated the effect of PDLSC-seeded HGCCS on bone repair in vivo. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 49 publications
7
57
0
2
Order By: Relevance
“…Besides, it has been hypothesized that dental follicle cells combined with ȕ-TCP bioceramics might become a novel therapeutic strategy to restore periodontal defects [934]. In still another study, the behavior of human periodontal ligament stem cells on a HA-coated genipin-chitosan scaffold in vitro was studied followed by evaluation on bone repair in vivo [935]. The study demonstrated the potential of this formulation for bone regeneration.…”
Section: A Clinical Experiencementioning
confidence: 98%
“…Besides, it has been hypothesized that dental follicle cells combined with ȕ-TCP bioceramics might become a novel therapeutic strategy to restore periodontal defects [934]. In still another study, the behavior of human periodontal ligament stem cells on a HA-coated genipin-chitosan scaffold in vitro was studied followed by evaluation on bone repair in vivo [935]. The study demonstrated the potential of this formulation for bone regeneration.…”
Section: A Clinical Experiencementioning
confidence: 98%
“…PDLSCs can be successfully isolated and cultured using single-cell-derived colony selection method [153]. When seeded onto HA scaffold, they can significantly improve calvarial bone repair [154].…”
Section: Periodontal Ligament--derived Stem Cells and Gingival Tissuementioning
confidence: 99%
“…Bone destruction can be caused by trauma, systemic disease, congenital abnormalities, and pathological conditions, such as in periodontitis, tumors, and cysts [1]. Bone destruction generally can cause significant bone loss and requires surgical treatment [2].…”
Section: Introductionmentioning
confidence: 99%